Analysis of Poverty Indices in Underdeveloped Countries: Nigeria Scenario - Otu, Judith. E. (Richtmann Publishing, 2011)
The socio-economic condition in Nigeria, present a perplexing paradox. In spite of a robust endowment in natural andhuman resources, the level of poverty of her people stands in contrast to the country’s enormous wealth. This paper seek to criticallyanalyse the poverty incident with specific reference to poverty incidence, poverty profile , poverty trend, type of poverty, measurement ofpoverty and the major causes of poverty in Nigeria. However, data were obtained from federal office of statistics and Central Bank ofNigeria (CBN) and the result shows that despite the abundant natural and human resources in Nigeria, the amazing paradox – acountry rich with plenty but occupied by people whom majority are perpetually poor and underdeveloped. Therefore, effective programmesmost be design if of poverty must be given a lasting solution in the area.